2019
DOI: 10.1111/gcb.14827
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative biomass curves describe past and present conditions of Large Marine Ecosystems

Abstract: Implementing the Ecosystem Approach in marine ecosystems is moving from preliminary steps—dedicated to defining the optimal features for indicators and developing efficient indicator frameworks—towards an operational phase where multisector marine management decisions are executed using this information. Within this operational context, emergent ecosystem properties are becoming quite promising as they have been demonstrated to be globally widespread and repeatable, and to be quite effective in detecting signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Ecosystemlevel reference points could also be an early warning of changes that would not be apparent in single-species reference points for many years, allowing for management prevention of changes to come or social preparation and adaptation (Link 2021). The ELRPs that track higher-level ecosystem functions can provide information on ecosystem conditions without needing to understand individual ecological processes (Link et al 2015;Link 2018;Schlenger et al 2018;Pranovi et al 2019). Ecosystem-level reference points can help managers balance competing objectives in management decisions by improving the ability to identify and understand potential adverse impacts on other parts of the system (Fulton et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ecosystemlevel reference points could also be an early warning of changes that would not be apparent in single-species reference points for many years, allowing for management prevention of changes to come or social preparation and adaptation (Link 2021). The ELRPs that track higher-level ecosystem functions can provide information on ecosystem conditions without needing to understand individual ecological processes (Link et al 2015;Link 2018;Schlenger et al 2018;Pranovi et al 2019). Ecosystem-level reference points can help managers balance competing objectives in management decisions by improving the ability to identify and understand potential adverse impacts on other parts of the system (Fulton et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Testing the theory with commercial marine fisheries capture or landings data as a proxy for biomass found that most marine systems exhibited the expected patterns (Libralato et al 2019;Pranovi et al 2019;Link 2021). Further, derived curve parameters (e.g., values of x and y at inflection points and slope; see Figure 4) for a single system tracked over time show patterns of perturbation and recovery.…”
Section: Ecosystem-level Reference Points Based On Ecosystem Trophic ...mentioning
confidence: 92%
See 3 more Smart Citations